Exploring the Impacts of Universal Design for Learning (UDL) on Reading Comprehension: A Systematic Review of Literature - EL Boukhrissi, Meriem; Brigui, Hind (International Journal of Language and Literary Studies, 2025)
Universal Design for Learning is a framework which advocates for inclusivity and encourages learning for all learners through the minimization of instructional barriers and the ensuring of flexibility (Rose & Gravel, 2010). The integration of Universal Design for Learning principles and guidelines in reading comprehension instruction has gained considerable attention in recent years for its potential to improve diverse students´ learning achievements. Employing the UDL principles´, teachers can design and adapt an effective learning curriculum that supports literacy for all learners. The aim of this systematic literature review is to synthesizes the current research on the effectiveness of UDL in enhancing reading comprehension outcomes for diverse learners. This study utilized six comprehensive scientific databases to identify pertinent studies. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, which will aid in the reporting and summarizing of the prevailing studies in a manner that is accurate and straightforward. 7 empirical studies were retrieved based on predefined criteria of inclusion, then the process of data extraction was managed using NVivo to extract relevant data from the studies. The findings revealed that UDL significantly improves the reading comprehension outcomes of diverse learners by providing multiple means of representation, engagement, and expression especially when supplemented with assistive technology and multimodal platforms. It has the potential to foster inclusive reading instruction; however, its successful integration is dependent on the presence of adequate teacher training, institutional support, and the demand for more resources to reinforce UDL´s implementation.